Kompetensi Pedagogik Tuhan Yesus dalam Injil Matius Pasal 5-7 - Ronald Yohanes Sinlae (Sekolah Tinggi Teologi Excelsius, 2019)
AbstractIn Matthew chapters 5-7 Jesus teaches His disciples on the Mount. Jesus does not need a particular school or building, every circumstance and meeting are always used to convey the word of God. In His Teaching, the Lord Jesus has the goal to discuss various topics about religion and morality in a scientific or theoretical manner and to serve everyone who comes to Him. Jesus knew and understood the Characteristics of the students and followers who were listening to His teachings. In the teaching process Jesus always taught in a special way. Jesus did not give a teaching and tell others to believe it, but encouraged them to think and draw their own conclusions about what had been explained to His disciples. Keywords: Pedagogical Competence; Lord Jesus; Gospel of Matthew Abstrak Di dalam Matius pasal 5-7 Yesus mengajar murid-murid-Nya di atas Bukit. Yesus tidak memerlukan sekolah atau gedung tertentu, setiap keadaan dan pertememuan selalu di gunakan untuk menyampaikan firman Allah. Dalam Pengajaran-Nya, Tuhan Yesus mempunyai tujuan untuk membahas berbagai topik tentang keagamaan dan kesusilaan secara ilmiah atau teori dan melayani setiap orang yang datang kepada-Nya. Yesus mengenal dan memahami Karakteristik murid-murid dan pengikut yang sedang mendengarkan pengajaran-Nya. Dalam proses pengajaran Yesus selalu mengajar dengan cara yang istimewa. Yesus tidak memberikan suatu ajaran dan menyuruh orang lain untuk mempercayainya, tetapi mendorong mereka untuk berpikir dan menarik kesimpulan sendiri atas hal yang telah dijelaskan kepada murid-murid-Nya. Kata kunci: Kompetensi Pedagogik; Tuhan Yesus; Injil Matius